The Influence Of Artificial Intelligence Literacy And Digital Competency Of Lecturers On The Effectiveness Of Islamic Education Learning At Islamic Religious Higher Education Institutions In Depok City - Badruddin; Muammar Zulfiqri (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah dan Ilmu Keguruan, Universitas PTIQ Jakarta, 2026)
This study aims to analyze the influence of Artificial Intelligence (AI) literacy and lecturers' digital competence on the effectiveness of Islamic education learning in Islamic higher education institutions in Depok City. A quantitative approach using a survey method was employed. The sample consisted of 120 active Islamic education lecturers selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire (1–5) that had been validated for reliability. Data analysis was performed using multiple linear regression with SPSS version 26. The results indicate that: (1) AI literacy positively and significantly influences learning effectiveness (β = 0.356; t = 4.215; p < 0.001); (2) digital competence positively and significantly influences learning effectiveness (β = 0.421; t = 5.102; p < 0.001); and (3) AI literacy and digital competence simultaneously and significantly influence learning effectiveness (F = 42.315; p < 0.001) with a coefficient of determination R² = 0.623. These findings imply that enhancing AI literacy and digital competence of lecturers is a strategic investment to improve the quality of Islamic education in the digital era, which must remain grounded in the values of adab, akhlaq, and Islamic ethics.